Pembuatan Media Promosi Untuk Kegiatan Karang Taruna Desa Senang Hati - Sylvana, Andi; Praningtyas, Elisabeth Ria Viana; Sunarsih, Nenah; Juwita, Rakhmini; Andriyansah, Andriyansah; Maesaroh, Imas; Ginting, Ginta; Riana, Kurnia Endah; Pujiwati, Ami; Hidayah, Zainur; Hadiwidjaja, Rini Dwiyani; Pujiastuti, Sri Lestari; Nasoha, Mohamad; Irmawaty, Irmawaty; Subekti, Rini (Abdimas Indonesian Journal, 2024)
Senang Hati Village is one of the developing villages in Malingping Sub-district, Lebak Regency, Banten Province, where the majority of the population is young. Unfortunately, the difficult road conditions in the village mean that young people are less interested in pursuing formal education as high as possible. In addition, the highest public school in Senang Hati Village is only up to junior high school level, so their knowledge and skills are very limited. This also makes the youth of Senang Hati Village lack a sense of responsibility and concern for their village. In fact, the progress of Senang Hati villagse is in the hands of these young people. Departing from the situation analysis, the Community Service Team (PkM) of the Universitas Terbuka (UT) Faculty of Economics and Business (FEB) lecturers provided training and assistance in making promotional media that could improve youth skills. These skills can become new jobs for young people so that Senang Hati Village can develop. Training and mentoring is carried out offline and online using Canva. The results of the training and mentoring showed that the youth of Senang Hati Village began to be able to use the Canva application properly. Now they have the initial skills that can support various village promotions and generate income, both for the village and for themselves. The training and mentoring can be continued until the youth of Senang Hati Village.